2021
DOI: 10.1016/j.tranon.2020.100872
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide activates nature killer cell-mediated antitumor responses by inhibiting IL-6/STAT3 signaling in hepatocellular carcinoma

Abstract: Inflammatory IL-6/STAT3 signaling is constitutively activated in diverse cancers and is associated with malignant cell proliferation, invasion and escape of antitumor immunosurveillance. Liraglutide, a glucagon-like peptide-1 (GLP-1) analog, is commonly used to treat insulin-resistant diabetes. In this study, for the first time, we showed that liraglutide remarkably improved the antitumor immune responses in hepatocellular carcinoma (HCC). Furthermore, we showed that the antitumor activity was mediated by natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The antitumor activity was mediated by nature killer (NK) cells, but not by CD8+ T cells. Furthermore, liraglutide increased NK-mediated cytotoxicity by suppressing the IL-6/STAT3 signaling pathway in HCC cells (65) .…”
Section: Medication and Lyfestylementioning
confidence: 93%
See 1 more Smart Citation
“…The antitumor activity was mediated by nature killer (NK) cells, but not by CD8+ T cells. Furthermore, liraglutide increased NK-mediated cytotoxicity by suppressing the IL-6/STAT3 signaling pathway in HCC cells (65) .…”
Section: Medication and Lyfestylementioning
confidence: 93%
“…Associated data on the use of glucagon-like peptide 1 (GLP-1) receptor agonists and sodium-glucose cotransporter 2 (SGLT2) inhibitors demonstrate improvement in NASH and NAFLD. Stud-ies carried out with cell culture and in mice showed that liraglutide suppressed liver carcinogenesis (64,65) . The antitumor activity was mediated by nature killer (NK) cells, but not by CD8+ T cells.…”
Section: Medication and Lyfestylementioning
confidence: 99%
“…GLP-1 receptors may also be expressed on hepatocytes to modulate insulin signaling and lipid metabolism [ 187 ], though this has been debated and liver effects may be indirect [ 188 , 189 ]. However, a number of studies have reported their presence in human hepatocytes and have demonstrated direct effects of GLP-1RAs on hepatocytes and HCC cell lines in vitro [ 187 , 190 , 191 , 192 , 193 , 194 ]. Preclinical animal models have also demonstrated their positive effects on liver lipid metabolism and NAFLD [ 190 , 195 , 196 , 197 ].…”
Section: Therapeutic Targets In Nafld and Nafld-related Hccmentioning
confidence: 99%
“…A recent systematic review of 24 completed and 8 ongoing clinical trials found strong evidence for the use of GLP-1RAs in the treatment of NAFLD patients [ 198 ]. Shifting focus to HCC, preclinical animal models demonstrate the antitumorigenic properties of GLP-1RAs [ 194 , 199 ]. The corresponding antitumorigenic effect in vitro using cell culture models support a direct and independent mechanism [ 192 , 193 , 194 ].…”
Section: Therapeutic Targets In Nafld and Nafld-related Hccmentioning
confidence: 99%
See 1 more Smart Citation